Direction of Delayed Solow-Verhulst Model with Fixed Labor Demand - ElFadily, S. (Journal of Applied Nonlinear Dynamics, 2026)
This paper deals with the Hopf bifurcation direction in a delayed Solow- Verhulst model Sahbani. The delay represents the time needed to assess needs for the labor force and the time taken for its recruitment. The direction of the Hopf bifurcation and the stability of the bifurcating periodic solutions are derived by applying the normal form method and center manifold theory. We also give numerical examples to motivate the proposal and illustrate our main result.